OCCURENCE OF HEXAVALENT CHROMIUM IN THE OPHIOLITE RELATED AQUIFERS OF LOYTRAKI AND SCHINOS AREAS - Pyrgaki, K.; Argyraki, A.; Kelepertzis, E.; Paraskevopoulou, V.; Botsou, F.; Dassenakis, E.; Mitsis, I.; Skourtsos, E. (Bulletin of the Geological Society of Greece, 2016)
The main objective of the present study is to assess Cr(VI) concentrations in groundwater and surface water of Loutraki and Schinos areas. Totally, 38 samples were collected from both areas from April to May 2015. Both surface water and groundwater are of bicarbonate-magnesium type (Mg-HCO3 -) and present very high concentrations of Mg2+ (up to 266mg/L) whereas the Cr(VI) concentrations vary among the different water groups (<1,6μg/L-120μg/L). Only 2 out of 15 boreholes of Loutraki area have chromium concentrations above the permissible level for drinking water (50μg/L for Cr(tot)) with the maximum Cr(VI) concentration being 74μg/L. In the area of Schinos, three wells have also high concentrations of Cr(VI) ranging from 40μg/L to 120μg/L. The absence of industrial activity in both areas is indicative of the geogenic origin of Cr(VI) in groundwater which is probably related to the dissolution and oxidation of primary Cr bearing minerals derived from ophiolithic rocks of Geraneia Mountains.